Teknologi dan Pendidikan Matematika - Aminah, Mimih (Infoman's, 2009)
Technologies based on dynamic interactive electronic media embody fundamental attributes that distinguish them from traditional static media in ways likely to have tremendous long- term impact why this might be the case. On the computer side of analogy, the rebuilding of classroom facilities and especially the redesign of classroom practice has only begun. School structures of all types (phisycal, scheduling, curriculum, materials development and dissemination, and so on) have been developed for the use of traditional media by all parties- teachers, students, administrators. Infrastructure is slow to change. Early uses of technologies are transliterations of exixting practice. Mature uses are barely hinted at in today’s practice.